Exploring complementary and alternative medicine (Richard and Hinda Rosenthal lectures, 2003)
Complementary and alternative medical (CAM) therapies encompass a broad spectrum of practices and beliefs. The NIH National Center for Complementary and Alternative Medicine (NCCAM) defines CAM as "healthcare practices outside the realm of conventional medicine, which are yet to be validated using scientific methods." Integrative medicine refers to ongoing efforts to combine the best of conventional and evidence-based complementary therapies while emphasizing the primacy of the patient-provider relationship and the importance of patient participation in health promotion, disease prevention, and medical management. The Dietary Supplement Health and Education Act (DSHEA) defines dietary supplements as products (other than tobacco) intended to supplement the diet that bear or contain one or more of the following dietary ingredients: a vitamin, mineral, amino acid, herb or other botanical; or a dietary substance for use to supplement the diet by increasing the total dietary intake; or a concentrate, metabolite, constituent, extract, or combination of any ingredient described above; and intended for ingestion in the form of a capsule, powder, soft gel, or gelcap, and not represented as a conventional food or as a sole item of a meal or the diet